Laser cladding process to enhanced surface properties of hot press forming die: A review - Norhafzan, B.; Khairil, C. M.; Aqida, S. N. (IOP Publishing, 2021)
Laser cladding is one of the advance processes in laser surface treatments. The process involved a laser beam to combines another material that has different metallurgical properties on a substrate, whereby a very thin layer of the substrate has to be melted for it to achieve metallurgical bonding with minimal dilution of added material and substrate. The resulted properties were characterized by surface topography, subsurface microstructure, hardness, and residual stresses. The objective of this paper is to review the factors that affected of cladding process to get the best cladding, suitable to enhance hot press forming die surface and subsurface. The parameter control, metallurgical bonding between coating and substrate, and effect of powder size were discussed.